Examining Primary School Teachers' Readiness Levels for Authentic Learning: A Mixed Methods Study - Aktepe, Vedat; Behriz, Abdullah; Bulut, Aydın (Participatory Educational Research (Per), 2025)
The objective of this study is to ascertain the preparedness levels of primary school educators for authentic learning and to evaluate this preparedness in relation to a range of variables. The study employed a mixed-methods design, integrating both quantitative and qualitative research techniques. In the quantitative dimension of the study, a survey method was employed, and the sample group consisted of 204 teachers selected through a non-probability sampling technique. The 'Authentic Learning Readiness Scale for Teachers' was employed as the instrument for the collection of data. The data were analysed using the statistical software package SPSS. Frequencies and mean values were examined, and an independent t-test and one-way analysis of variance (ANOVA) were used to determine any significant differences. The quantitative results of the study indicated that primary school teachers exhibited a high level of readiness for authentic learning, with no significant differences observed across gender, age, professional seniority, education level, class size, or place of duty variables. In the qualitative dimension of the study, the phenomenological method was employed, and the study group was determined using criterion sampling. A semi-structured interview format was employed as the primary data collection instrument. The data were collected from 13 teachers who participated in focus group interviews and subsequently analysed using MAXQDA content analysis software. The qualitative results of the study indicated that primary school teachers associated authentic learning with activities that were related to students' lives and learning through doing and experiencing.